Effect of nitrogen seeding on the energy losses and on the time scales of the electron temperature and density collapse of type-I ELMs in JET with the ITER-like wall. (21st January 2015) - Frassinetti, L.; Dodt, D.; Beurskens, M.N.A.; Sirinelli, A.; Boom, J.E.; Eich, T.; Flanagan, J.; Giroud, C.; Jachmich, M.S.; Kempenaars, M.; Lomas, P.; Maddison, G.; et al.
Abstract: The baseline type-I ELMy H-mode scenario has been re-established in JET with the new tungsten MKII-HD divertor and beryllium on the main wall (hereafter called the ITER-like wall, JET-ILW). The first JET-ILW results show that the confinement is degraded by 20–30% in the baseline scenarios compared to the previous carbon wall JET (JET-C) plasmas. The degradation is mainly driven by the reduction in the pedestal temperature. Stored energies and pedestal temperature comparable to the JET-C have been obtained to date in JET-ILW baseline plasmas only in the high triangularity shape using N2 seeding. This work compares the energy losses during ELMs and the corresponding time scales of the temperature and density collapse in JET-ILW baseline plasmas with and without N2 seeding with similar JET-C baseline plasmas. ELMs in the JET-ILW differ from those with the carbon wall both in terms of time scales and energy losses. The ELM time scale, defined as the time to reach the minimum pedestal temperature soon after the ELM collapse, is ∼2 ms in the JET-ILW and lower than 1 ms in the JET-C. The energy losses are in the range Δ W ELM / W ped  ≈ 7–12% in the JET-ILW and Δ W ELM / W ped  ≈ 10–20% in JET-C, and fit relatively well with earlier multi-machine empirical scalings of Δ W ELM / W ped with collisionality. The time scale of the ELM collapse seems to be related to the pedestal collisionality. Most of the non-seeded JET-ILW ELMs are followed by a further energy drop characterized by a slower time scale ∼8–10 ms (hereafter called slow transport events), that can lead to losses in the range Δ W slow / W ped  ≈ 15–22%, slightly larger than the losses in JET-C. The N2 seeding in JET-ILW significantly affects the ELMs. The JET-ILW plasmas with N2 seeding are characterized by ELM energy losses and time scales similar to the JET-C and by the absence of the slow transport events.